Proceedings of the International Scientific Conference - Sinteza 2017 2017
DOI: 10.15308/sinteza-2017-169-175
|View full text |Cite
|
Sign up to set email alerts
|

Neural Model for Far-Field 1D Localization of Mobile Stochastic EM Sources with Partially Correlated Radiation

Abstract: Abstract:This paper considers a possibility of angle position determination of mobile stochastic sources with partially correlated radiation, where antenna array and multilayer perceptron neural network processing are used. It is shown that the neural model trained with samples from a system with uncorrelated source radiation cannot determine position of sources with a satisfactory accuracy when sources have some degree of correlation in radiation. That is why it is suggested training samples to be generated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…In all these references, neural models were applied for the DoA estimation of deterministic signals radiated from mobile electromagnetic (EM) sources. Multilayer perceptron (MLP) neural networks were also used for the DoA estimation of deterministic and stochastic EM sources . Regarding the stochastic scenario, in References uncorrelated mobile stochastic sources were considered and it was shown that only the values of elements of the first row of spatial correlation matrix at the receiver were sufficient to develop an accurate neural model.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In all these references, neural models were applied for the DoA estimation of deterministic signals radiated from mobile electromagnetic (EM) sources. Multilayer perceptron (MLP) neural networks were also used for the DoA estimation of deterministic and stochastic EM sources . Regarding the stochastic scenario, in References uncorrelated mobile stochastic sources were considered and it was shown that only the values of elements of the first row of spatial correlation matrix at the receiver were sufficient to develop an accurate neural model.…”
Section: Introductionmentioning
confidence: 99%
“…All models presented in References were developed with an assumption that stochastic sources are with equal and constant radiation power during their movement. The architecture of the neural model that includes the possibility to perform the DoA estimation of signals emitted from movable stochastic sources with variable radiation powers was given in Reference .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations